Rethinking water user associations to enhance women’s participation - Fanaian, Safa; Bhattacharjee, Suchiradipta; Waqar, Kanwal; KC, Sumitra (2025)
Studies from the International Water Management Institute on Water User Associations (WUAs) across South Asia show that while barriers for women persist, change is possible and scalable. This article explores why women’s participation matters, the challenges they face, and how processes can be redesigned and scaled to make WUAs truly inclusive and effective.